IMPLEMENTASI KONSEP PDCA DAN SEVEN TOOLS UNTUK MENGURANGI REJECT PRODUK V-BELT DI PT. BANDO INDONESIA - Dahniar, Tedi; Ibnu, Fredy Dwi; Zulziar, Marjuki (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2022)
ABSTRACTThe trend of selling automatic motorbikes is superior to Sports motorbikes and motorbikes every year. To maintain consumer confidence to produce quality products and be able to compete, in its production activities, the company always strives to produce good products and reduce product damage, but the reality in the field is that many products that are produced are not following the standards that have been set. PT. Bando Indonesia is a manufacturing company engaged in the automotive sector, especially automotive belt components and the electric transmission industry, motorcycles, and cars. The product type is the V-Belt. This study aims to analyze how the implementation of quality control using PDCA tools (Plan, Do Check, Action) and seven tools are used to reduce defects and problems faced by the production department by controlling the level of product damage in the company. After correcting the factors causing the problem, the Air Bubble Defect was successfully reduced from 2397 to 669 pcs. Thus the quality control activities carried out succeeded in solving problems that occurred in the V-Belt production process